The Alqueva reservoir in Portugal: towards the development of a new lake destination. - Rodrigues, Ana Isabel (2013)
A number of well-known tourism destinations around the world are based on lakes as the main attraction. Although is still difficult to determine the economic significance of lakes, lake tourism has been recognized as a relevant sub-field of tourism studies. Based on a PhD investigation related to lake tourism, this paper seeks to reveal and discuss the potential of the Alqueva reservoir as an emerging destination in the Alentejo region in the south of Portugal. This new resource has offered a naturally defined unit for tourism development since the reservoir started to fill up in 2002. Further research concerning destination image applied to the Alqueva Lake as a study area will provide valuable information for positioning and promoting it as a lake-destination in the future. Meanwhile, some of the challenges and contradictions in aligning the Alqueva as a resource with tourism development are highlighted in this paper